Akuntabilitas Penasihat Khusus, Utusan Khusus, dan Staf Khusus pada Lembaga Kepresidenan: Sebuah Evaluasi - Akhyaroni Fu’adah (Fakultas Hukum Universitas Islam Indonesia, 2025)
This study evaluates the regulations concerning special advisors, special envoys and special staff to the President and/or Vice President in Indonesia, as well as their implementation. The accountability mechanism only emphasises superiors, which hinders the implementation of accountable governance, despite the fact that the Presidency's organs were formed to support the implementation of executive duties and functions. In contrast, the United States has the Federal Advisory Committee Act (FACA), which provides guidelines for committees or advisory bodies formed by the President to ensure that their duties and authorities are accountable and transparent to the public. The study aims to examine how institutional structuring affects a country's constitutional system. This study employs normative research with secondary data, which will be analysed using a comparative method against the United States. Ultimately, the study concludes that integrated presidential institution regulations would clarify the duties, authorities and responsibilities of each organ.